An examination of the Vietnamese emerging market economy: understanding how and why auditors have responded to the audit law reforms. (13th May 2019) - Nguyen, Phuong Thi; Kend, Michael
Abstract: Using New Institutional Sociology (NIS), we seek to explain the variation between what was intended with the Vietnamese reforms to audit in 2011 and the actual practice, and why there is variation. This paper reports findings from interviews with 70 individuals representing identified groups of stakeholders in the market for audit and assurance services in Vietnam. Overall, the findings indicate that there still exist business risks for foreign companies that pursue trade and commerce in communist Vietnam, particularly where non‐Big 4 audit firms are involved in the external audit function, as in some cases auditor independence is most likely compromised.